HYPOCHOLESTEROLEMIC EFFECT AND PIGMENTS COMPOSITION OF HERBAL MEDICINE CONTAINING HIGHER AND LOWER PLANTS - Limantara, Leenawaty; Indrawati, Renny; Wijaya, Dian Ekawati; Sulistiawati, Erni; Suparto, Irma Herawati; Wijayanti, Retno Dumilah Esti; Brotosudarmo, Tatas Hardo Panintingjati (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: The objective of this research was to investigate the antihypercholesterolemic activity of herbal medicine which consisted of pigment-rich simplicia from higher and lower plants, as well as to determine its pigments composition. Methods: Sprague-Dawley male rats were randomly divided into five cholesterol-rich diet groups as well as one negative control group with a normal diet, in order to investigate its effect on plasma lipid. The new herbal formulation was administered orally to induced-rats at three dosage levels, whereas simvastatin was used as a comparable generic drug. Pigments composition was determined by means of reversed-phase high-performance liquid chromatography (HPLC) using gradient protocol, monitored with diode array detector at 430 nm. Results: The administration of herbal medicine was able to significantly reduce total plasma cholesterol and low-density lipoprotein-cholesterol (p<0.05) at a dose of 312.5 mg/kg of body weight/day compared to positive control group, and hence the atherogenic index was also lowered. The chromatographic analysis of pigments determination and quantification are reported correspondingly to support the possible active compounds data of hypocholesterolemic property. Conclusion: The results obtained in this research work indicated the potency of pigment-rich lower plants to substitute the obtrusive exploration and dominant use of higher plants for treating dyslipidemia.Â 